The Job Related Factor and Organizational Commitment at PTPL College Sungai Petani, Kedah - Nurul Jannah, Zulkifly (2014)
The main purpose of this study was to evaluate the relationship between job role with the commitment of employees within an organization. This study will try to find the relationship between the sub dimensions of work role and its relationship with organizational commitment supervisor support, colleague support, access to resources and the role of employees. The research questions are developed based on questionnaires 'Organizational Commitment Questionnaire' (OCQ) introduced by, Steers, and Porter Moday, 1979, which aims to find the level of organizational commitment among employees. Question consists of 44 items using a Likert scale where it would involve the 63 respondents in this study. All data were analyzed using the Statistical Package for Social Sciences (SPSS) version of twenty. In this study, it has two types of statistical analysis used descriptive statistics, to see the percentages and inferential statistics using Pearson correlation for the relationship between variables. This study expects that PTPL College Sg. Petani can maintain a high level of organizational commitment is to ensure that the company will be more productive and more competitive in the future through the study in the future.